2019
DOI: 10.1371/journal.pone.0222976
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of potato tubers (Solanum tuberosum L.) as a consequence of genetic potential and growing conditions

Abstract: The concentrations of the bioactive compounds in potato tubers are determined by both genetic potential and environmental factors. The purpose of the experiment was to determine the influence of organic and integrated production on the expression of the genetic potential with respect to the antioxidant properties of potato tubers and to evaluate its stability under different environmental conditions. This phenotyping was performed on seven new breeding lines (tetraploid clones) and three modern cultivars: Jell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 37 publications
(59 reference statements)
2
21
0
Order By: Relevance
“…Kazimierczak et al [154] reported significantly higher contents of flavonoids, quercetin, and quercetin-3-O-rutinoside in organically grown potato tubers compared to the conventionally grown tubers. Conversely, Brazinskiene et al [153] found that the farming system had no significant effect on phenolic acid concentrations in the potato tubers while Keutgen et al [163] found higher contents of phenolic compounds, flavonoids, and ascorbic acid in organically grown potato tubers than the conventionally grown potato tubers. Romero-Pérez et al [231] found that flavonoids in plants are strongly impacted by genotype, the agroclimatic conditions, and the cultivation system.…”
Section: Bioactive Compounds and Antioxidants Content In Potato Tubersmentioning
confidence: 97%
“…Kazimierczak et al [154] reported significantly higher contents of flavonoids, quercetin, and quercetin-3-O-rutinoside in organically grown potato tubers compared to the conventionally grown tubers. Conversely, Brazinskiene et al [153] found that the farming system had no significant effect on phenolic acid concentrations in the potato tubers while Keutgen et al [163] found higher contents of phenolic compounds, flavonoids, and ascorbic acid in organically grown potato tubers than the conventionally grown potato tubers. Romero-Pérez et al [231] found that flavonoids in plants are strongly impacted by genotype, the agroclimatic conditions, and the cultivation system.…”
Section: Bioactive Compounds and Antioxidants Content In Potato Tubersmentioning
confidence: 97%
“…e main characteristic of plants under stress is the imbalance of active oxygen metabolism. e dynamic balance between the generation and elimination of reactive oxygen species in plants is broken, so reactive oxygen species gradually accumulate in plant cells, thus damaging plant cells, and even death in severe cases [7]. SOD, pod, and cat are the main enzymes for scavenging reactive oxygen species in plants.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] The phytoconstituents present in both the pulp and peel of potatoes, such as polyphenols, are characterized for possessing antioxidant, antiinflammatory, and antimicrobial properties. [38][39][40][41][42] The presence of these phytoconstituents would be responsible for promoting the evolution of wound closure until day 7 of treatment, observing that the groups that received the application of S. tuberosum ointments showed an acceleration in wound closure compared to the negative control and positive control groups (Figure 2).…”
Section: Discussionmentioning
confidence: 99%